Cumulative behavioral and metabolic determinants of health are associated with higher inflammation-related indices: insights from a cross-sectional study (NHANES 2005–2018) - Wang, Anzhi; Zeng, Youping; Gao, Xiaoyan; Lin, Xunge; Du, Shenshen; Wang, Ping; Pan, Yun (Frontiers in Public Health, 2025)
ObjectiveThis study innovatively investigates the cumulative associations between behavioral determinants of health (BDoH), metabolic determinants of health (MDoH), and systemic inflammation biomarkers in U.S. adults, using a novel cross-sectional framework to quantify their synergistic effects.MethodsUtilizing cross-sectional data from 18,500 participants in the National Health and Nutrition Examination Survey (NHANES 2005–2018 cycle), we developed a composite exposure model integrating BDoH (smoking status, physical activity, dietary quality) and MDoH (obesity metrics, hypertension, diabetes) through standardized questionnaires and clinical measurements. Systemic immune-inflammation index (SII) and systemic inflammatory response index (SIRI) were calculated from peripheral blood cell counts. Multivariable-adjusted logistic regression models examined dose–response relationships, with trend analysis explicitly testing cumulative BDoH-MDoH interactions.ResultsThe cohort (mean age 44.3 ± 0.3 years; 52.4% male) demonstrated significant positive associations between adverse health determinants and inflammatory indices. Current tobacco use (OR = 1.32, 95%CI = 1.18–1.47), suboptimal diet (HEI < 52: OR = 1.24, 95%CI = 1.11–1.38), obesity (BMI ≥ 30 kg/m2: OR = 1.41, 95%CI = 1.27–1.56), and central adipometry (OR = 1.39, 95%CI = 1.25–1.54) showed strongest correlations with elevated SII/SIRI. Metabolic disorders exhibited distinct patterns: hypertension and diabetes associated specifically with SIRI elevation (OR = 1.19, 95%CI = 1.06–1.33 and OR = 1.17, 95%CI = 1.03–1.32, respectively), while physical inactivity (<600 MET-min/week) uniquely correlated with SII increase (OR = 1.26, 95%CI = 1.13–1.40). Notably, our cumulative model revealed synergistic effects: exposure to ≥3 adverse behavioral determinants amplified inflammation risks (SII: OR = 1.57, 95%CI = 1.42–1.73; SIRI: OR = 1.49, 95%CI = 1.35–1.64), with significant dose-dependent trends (P-trend<0.001). Co-occurring metabolic abnormalities demonstrated additive inflammatory effects (P-trend<0.001), exceeding individual risk factor impacts.ConclusionThis cross-sectional study provides the first evidence that integrated BDoH-MDoH cumulative exposure models uncover distinct and synergistic inflammatory pathways. Both individual and combined behavioral-metabolic risk factors significantly associate with systemic inflammation biomarker elevation, highlighting the necessity of dual-target intervention strategies.